Revitalisasi Hukum Adat dalam Penyelesaian Sengketa Lingkungan Studi Komparatif di Wilayah Adat Indonesia Timur - Sinaga, Febrian Jeki Elfian; Panjaitan, Sairimbun; Hafiza, Lana (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2025)
This study explores the revitalization of customary law as a mechanism for resolving environmental disputes in Eastern Indonesia. Through a comparative analysis of three indigenous regions—Central Maluku, Papua, and West Timor—the research reveals how traditional legal practices adapt to contemporary ecological and socio-political challenges. The findings demonstrate that customary law is not merely preserved but is actively transformed to maintain cultural relevance and environmental sustainability. Revitalization efforts are shaped by local contexts, external pressures, and the interaction between indigenous communities and state institutions. This study fills a critical gap in the existing literature, which often focuses solely on the formal recognition of customary law without addressing its dynamic role in conflict resolution. Although the research offers significant insights, it acknowledges limitations related to geographical scope and methodology, suggesting that future studies should adopt longitudinal approaches and broader regional coverage. The results contribute to the discourse on legal pluralism and offer practical implications for policy-making aimed at strengthening indigenous participation in environmental governance.